Impact of hydrogel-based airway management strategies on ventilator-associated pneumonia: clinical applications and future directions - Xu, Yong; Zhao, Baisong (Frontiers in Materials, 2025)
This review discusses the current applications of hydrogels in the management of airway lung injury and ventilator-associated pneumonia (VAP), with a particular focus on their potential impact in clinical practice. Research indicates that hydrogel technology can not only enhance airway management and promote lung tissue repair but also significantly reduce the risk of infection. For instance, clinical trials have shown that hydrogel-coated endotracheal tubes are effective at reducing the incidence of VAP, with related data indicating a reduction of up to 30%. Furthermore, we analyze the limitations of current research and propose directions for the future development of hydrogel-based therapies in this important field of respiratory medicine.